TIỀM NĂNG SỬ DỤNG KÊNH HÌNH TRONG DẠY HỌC MÔN “SÁNG TÁC THƠ CA” Ở KHOA NGỮ VĂN, TRƯỜNG ĐẠI HỌC SOUPHANOUVONG (LÀO) - Bounchan KEOMANYKHA (Tạp chí Giáo dục, 2023)
The subject of Poetry Creation plays an important role in the education curriculum of high school and universities in Laos. Visual means can support and encourage the cognitive and creative process in teaching poetry creation. This article discusses about significant visual means that can be effectively used in teaching this subject at the Faculty of Philology, Souphanouvong University (Laos)